2014
DOI: 10.1371/journal.pone.0095908
|View full text |Cite|
|
Sign up to set email alerts
|

Gastroprotective Activity of Ethyl-4-[(3,5-di-tert-butyl-2-hydroxybenzylidene) Amino]benzoate against Ethanol-Induced Gastric Mucosal Ulcer in Rats

Abstract: BackgroundThe study was carried out to determine the cytotoxic, antioxidant and gastro-protective effect of ethyl-4-[(3,5-di-tert-butyl-2-hydroxybenzylid ene)amino] benzoate (ETHAB) in rats.Methodology/Principal FindingsThe cytotoxic effect of ETHAB was assessed using a MTT cleavage assay on a WRL68 cell line, while its antioxidant activity was evaluated in vitro. In the anti-ulcer study, rats were divided into six groups. Group 1 and group 2 received 10% Tween 20 (vehicle). Group 3 received 20 mg/kg Omeprazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 42 publications
7
21
0
Order By: Relevance
“…Our data indicate that significant protection of stomach wall mucosa and decreases in ulcer area are observed in rats pre-fed with C. barometz extract. Our observation is consistent with the findings of several other studies [4, 12, 24]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our data indicate that significant protection of stomach wall mucosa and decreases in ulcer area are observed in rats pre-fed with C. barometz extract. Our observation is consistent with the findings of several other studies [4, 12, 24]. …”
Section: Discussionsupporting
confidence: 94%
“…The acid contents were expressed as meq/l. For each rat, the mucosa of stomach wasscraped slightly using the histological section slides, and the mucus in each stomach was weighed using the electronic balance [24]. …”
Section: Methodsmentioning
confidence: 99%
“…In the PAS staining assessment, this study demonstrated that C. barometz extract heightened the content of glycoprotein in the gastric mucosa (the magenta color). The increase in the production of mucus was an indicator of local gastric mucosal defence, which is consistent with the reports published by many investigators 29,63–65. Immunohistochemistry results indicated that pretreatment of rats with C. barometz extract produced upregulation of HSP70 protein, which protected the cells from oxidative stress or heat shock.…”
Section: Discussionsupporting
confidence: 91%
“…SOD mainly converts harmful superoxide anion into less dangerous hydrogen peroxide. 25 In the mucosa, the GSH system serves as an anti-oxidative barrier, and GSH acts as a reductant and co-factor for some antioxidant enzymes. 26 In our present study, challenge of ethanol induced a marked oxidative stress, as evidenced by elevated MDA levels and lowered both SOD and GSH levels in the gastric homogenate and serum (P < 0.01, Fig.…”
Section: Discussionmentioning
confidence: 99%